Secondary Hemophagocytic Lymphohistiocytosis With Epstein–Barr Virus-Associated Transformed Follicular Lymphoma: A Case Report and Literature Review - Xu, Huan; Xu, Xia; Cui, Guohui; Fang, Jun; Chen, Wanxin; Xue, Mei; Jin, Runming; Chen, Hongbo; Zhang, Lu; Hu, Yu (Frontiers in Oncology, 2021)
A 58-year-old male was admitted to our hospital due to lasting fever, progressive lymphadenopathy and bicytopenia, with a previously histological diagnosis of follicular lymphoma grade 3a with Epstein-Barr virus-encoded RNA positive one month ago. A second biopsy of axillary lymph node revealed concurrent diffuse large B-cell lymphoma with Epstein-Barr virus-encoded RNA positive. Another diagnosis of hemophagocytic lymphohistiocytosis secondary to Epstein-Barr virus positive diffuse large B-cell lymphoma was further concluded by clinical manifestation, laboratory test and atypical lymphocytes in peripheral-blood smear. After a pulse of steroids prephase treatment, the patient’s clinical condition deteriorated and died in a week. Presence of Epstein-Barr virus infection in patients with follicular lymphoma is associated with more aggressive clinical course and increased risk of high-grade transformation. Hemophagocytic lymphohistiocytosis in response to Epstein-Barr virus infection or lymphoma remains fatal. Early diagnosis and initiation of treatment may improve the outcome.